Degradation of textile effluente by fenton reaction - Lustosa, G. M.M.M. [UNESP]; Moita Neto, J. M. [UNESP]; Da Silva, C. E. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2013)
Advanced Oxidation Processes are widely used for the degradation of organic compounds in wastes that are resistant to conventional treatments and difficult biodegradability. The effluents from textile industry are unsuitable for conventional treatment, because the color is persistent and must be removed before the release of same in water bodies. To this, we used the Fenton reaction, making use of hydrogen peroxide and iron salts in various proportions. For each ratio was established a 20-minute interval, a total of 120 minutes. The color removal of textile wastewater was observed in the ratio 1:5 [Fe 2+]:[H2O2] and reaching 85,12% of removal.
Degradação de efluente têxtil pela reação de fenton
Keywords: Degradation; Effluents; Oxidation